Management Of Madrasah Supervisors POKJAWAS in Deli Serdang District - Ramadhani, Muhammad Luthfie; Munawwarah, Hidayatul (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2023)
Deli Serdang, a densely populated area with a majority Muslim faith, has many madrasah in various sub-districts. To get quality graduates, good learning processes, quality teachers and madrasa management, supervisory management is needed to guarantee and improve the quality of madrasah. After the pandemic, it has required a number of groups to create various concepts for organizing activities so that they do not experience setbacks, one of which is the concept of madarasah supervision management at the Deli Serdang Ministry of Religion. This research uses a qualitative approach with various conditions and stages of research methodology where the Pokjawas or Supervisory Working Group is the research object. The research results show that the management of the Pokjawas related to the supervisory work program is still being carried out but the presence of members is incomplete due to concerns during the Pandemic era. So regarding the use of program funds, Pokjawas activities still rely on independent funds from supervisors and self-help from a number of groups to carry out madrasa supervision programs, and the last is the responsibility of a number of supervisors regarding madrasa development. new strategy to facilitate coordination other than the online system between supervisors within the Pokjawas Ministry of Religion Deli.